Silicon‐containing trifunctional and tetrafunctional cyanate esters: Synthesis, cure kinetics, and network properties. Issue 6 (18th December 2013) - Guenthner, Andrew J.; Vij, Vandana; Haddad, Timothy S.; Reams, Josiah T.; Lamison, Kevin R.; Sahagun, Christopher M.; Ramirez, Sean M.; Yandek, Gregory R.; Suri, Suresh C.; Mabry, Joseph M.
ABSTRACT The synthesis and physical properties of new silicon‐containing polyfunctional cyanate ester monomers methyl[tris(4‐cyanatophenyl)]silane and tetrakis(4‐cyanatophenyl)silane, as well as polycyanurate networks formed from these monomers are reported. The higher crosslinking functionality compared to di(cyanate ester) monomers enables much higher ultimate glass transition temperatures to be obtained as a result of thermal cyclotrimerization. The ability to reach complete conversion is greatly enhanced by cocure of the new monomers with di(cyanate ester) monomers such as 1, 1‐bis(4‐cyanatophenyl)ethane. The presence of silicon in these polycyanurate networks imparts improved resistance to rapid oxidation at elevated temperatures, resulting in char yields as high as 70% under nitrogen and 56% in air in the best‐performing networks. The water uptake in the silicon‐containing networks examined is 4–6 wt % after 96 h of immersion at 85 °C, considerably higher than both carbon‐containing and/or di(cyanate ester) analogs. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 767–779